2015
DOI: 10.4254/wjh.v7.i26.2636
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to optimize the use of marginal donors in liver transplantation

Abstract: Liver transplantation is the treatment of choice for end stage liver disease, but availability of liver grafts is still the main limitation to its wider use. Extended criteria donors (ECD) are considered not ideal for several reasons but their use has dramatically grown in the last decades in order to augment the donor liver pool. Due to improvement in surgical and medical strategies, results using grafts from these donors have become acceptable in terms of survival and complications; nevertheless a big debate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 119 publications
(187 reference statements)
0
35
0
1
Order By: Relevance
“…3 In consideration of the prolonged time required for arterial reconstruction at back table, every effort should be made to minimize cold ischemia time, since a time > 12 hours is associated with a 2-fold higher risk of graft failure. 5 …”
Section: Discussionmentioning
confidence: 99%
“…3 In consideration of the prolonged time required for arterial reconstruction at back table, every effort should be made to minimize cold ischemia time, since a time > 12 hours is associated with a 2-fold higher risk of graft failure. 5 …”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the previous study findings, Pezzatiet al (2015) revealed that the implementation of transplant intervention educational program, lead to significant improvements in their performance related to measuring vital signs. [41] In addition, Neuberger and colleagues (2009) mentioned that there was significant improvement observed liver function and body weight of liver transplant recipients after liver transplantation due to reduced ascites. [42] Similar for these results study done by Feng et al [43] Majority of the studied sample reported pain pre transplantation are improved after implementation of program.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Therefore, extended criteria donors (ECDs), previously known as marginal donors, are more often accepted to augment the donor pool. (17) Living Donor Liver Transplantation in Germany LT from living related donors is a relatively common procedure in Germany for pediatric patients. (18) Overall, LDLTs account for far less than 10% of all LTs in adults (Fig.…”
Section: Referral and Assessment For Transplantation: Selection And Amentioning
confidence: 99%